Efectividad de las medidas afirmativas destinadas a los adultos mayores dentro de los centros gerontológicos del cantón Ibarra durante el año 2022 - Narváez Guerrero, Hefziba Daniela (2024)
The public policies implemented for the improvement of the quality of life of older adultshave been a great challenge to be performed in the best way. For this reason the great interest on the research entitled 'Effectiveness of affirmative measures for older adults within the gerontological centers of the canton Ibarra during the year 2022, whose objective was to identifyif the affirmative measures were properly employed by the government are solvent for this groupof vulnerable people, who need to supply a large amount of needs, and in such a way to distinguish if the performance of the state in terms of guaranteeing the rights of older adults, through norms, laws and public policies, are rigorously fulfilled, therefore the results of this research breaking down many inconsistencies on the part of institutionsthat do not fully provideresources for this group of older adults. In conclusion we can deduce that the elderly are not inthe best conditions to have the necessary and equally to be able to reach the last days of his lifein a dignified manner.